Intelligence Strategies in Mitigating National Security Threats in the Land Sector - Muhamad Ilyas Ruhiyat (Security Intelligence Terrorism Journal (SITJ), 2026)
Introduction: Land issues in Indonesia have developed into national security threats affecting political, economic, social, defense, and environmental sectors. Land ownership conflicts, document forgery, illegal land occupation, land mafia practices, and vulnerabilities in electronic data security indicate that land problems are no longer limited to administrative matters, but have influenced national stability. Therefore, an intelligence strategy is needed to support the prevention and mitigation of threats in the land sector. Methods: This study employed a descriptive qualitative approach through interviews, literature reviews, and document analysis. Informants consisted of representatives from the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency, State Intelligence Agency, National Cyber and Crypto Agency, law enforcement institutions, and judicial institutions. Data were analyzed qualitatively with the assistance of Nvivo 12 Pro software. Results: The findings show that threats in the land sector are both tangible and latent. Tangible threats include document forgery, overlapping ownership claims, land conflicts, and the potential for violence, while latent threats involve unequal land ownership, declining public trust, land mafia practices, and cybersecurity threats. Intelligence strategies are implemented through investigation, security, and public engagement functions by utilizing data based monitoring, document verification, strengthening electronic system security, and interagency coordination. Conclusion: Land related issues have become national security threats that require strategic and integrated approaches. Intelligence strategies play an important role in supporting early detection, data protection, conflict mitigation, and strengthening national stability. The success of these strategies depends on the readiness of human resources, technological capacity, cybersecurity resilience, institutional integrity, and interagency coordination.